Legal Regulations for Children Involved in Narcotics Crimes in Indonesia - Suryani Guntari; Kusbianto Kusbianto; Azmiati Zuliah; Ariman Sitompul (SEIKAT: Jurnal Ilmu Sosial, Politik dan Hukum, 2024)
Norms that protect children as perpetrators or victims, especially narcotics, are basically complete, namely the application of Law No. 35 Of 2009 On Narcotics Against Children Involved In Narcotics Crimes After The Birth Of Law No. 11 of 2012 on Child Protection. Seeing the verdict against the child offender who should be given protection, on the other hand the child protection rules strongly emphasize that children should not be reduced let alone deprived of their independence. The research method uses empirical juridical approach, the data used is secondary data and primary data. The interviewees in this study consisted of interviews with judges, investigators, child lawyers, social workers from Child Protection institutions. The data analysis used is qualitative. The provisions stipulated in law No. 35 of 2009 this of course applies in general but if involved in narcotics crime is a child then it is mandatory to use the Child Act. Before the birth of Law No. 11 of 2012 on the juvenile criminal justice system, the law used in the event law is law No. 3 year 1997 namundalam practice when the procedural law is regulated in the Narcotics Crime Act then used by investigators is the Narcotics Act while the Act No. 3 of 1997 on Juvenile Court impressed only as a companion to the law.